Health risk assessment via consumption of Pb and Cd contaminated vegetables collected from fresh markets in the lower north of Thailand. Issue 3 (2nd April 2016) - Wachirawongsakorn, Piyada
ABSTRACT: This study aimed to investigate the Pb and Cd contamination and health risk assessment for population via consumption of vegetables sold in fresh markets around the lower north of Thailand. The concentrations of Pb and Cd in various vegetables such as root/tuber, stem, inflorescence, fruit, and leaf vegetables were analyzed using an atomic absorption spec-trophotometer. Human health risks of these metals in vegetables were assessed based on target hazard quotient (THQ). The results indicated that more than 80% of the Pb and Cd in almost all vegetable samples exceeded the maximum allowable concentration by National Food Institute criteria with an average range of 0.96–3.39 and 0.48–1.40 mg/kg, respectively. The estimated daily intakes (EDI) of Pb and Cd via dietary consumption of vegetables were between 0.001–0.010 and 0.002–0.008 mg/kg/d, respectively. All EDIs of Pb contaminated vegetables were higher than the reference dose recommended by the USEPA except for leaf edible vegetables, while all EDIs of Cd contaminated vegetables were higher than the reference dose recommended by the USEPA. THQ indicated that the consumption of Pb contaminated root/tuber, stem, inflorescence, and fruit edible vegetables and Cd contaminated leaf vegetable for the local population in the lower north of Thailand could be a severe health risk problem.